Effect Of Return On Asset And Return On Equity On Price To Book Value In Automotive Subsector Manufacturing Companies Listed On The Indonesia Stock Exchange - Ancela Ayusari Bondar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2023)
The value of the company reflects the value of a company. Where the financial statements will be analyzed with Return On Asset and Return On Equity which is the benchmark to know the amount of the Company's ability to meet short and long-term obligations on the company. Research objects used as samples of automotive companies and listed on the Indonesia Stock Exchange as many as 9 Companies. The results of the ROA hypothetical test study have a t count of 4,092 and a sifnifikan value of 0.000. If the significant value is less than or equal to 0.05 (< 0.05) then the hypothesis is accepted. The results of the study obtained a value of 0.000 <0.05, it can be concluded that roa variables varsially affect the Price to Book Value in automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange.Variabel ROE has a t count of 8,815 with a significant value of 0.001<0.05. The results of significant tests (f-tests) in accordance with the basis of decision-making in test f can be shown that ROE simultaneously affects PBV. The correlation coefficient (R) value is 0.375 meaning that the relationship of variable X to variable Y in the category is less meaningful. Based on the test results of the naili determination coefficient adjust R Square in the regression model in automotive subsector manufacturing companies obtained by 42,3% PBV influenced by both free variables namely ROA and ROE. While the remaining 57,7% was influenced by other factors outside the model that were not studied in this study.